Host Density Influence on Regularly Fallen Lichen Species in Temperate Forests of Kumaun Himalaya - Kumar, Balwant; Arya, Mahesh Kumar; Arya, Vijay (Indian Forester, 2022)
Lichens are very slow growing plants and play a significant role in forest ecosystem. In temperate areas lichens occur abundant on Quercus trees. After falling down lichens decompose into the soil and contribute in nutrient cycling. In the present study nine regularly fallen lichen species were recorded in three altitudinal zones. The density of fallen lichen was found maximum 95625 ind. ha-1 yr-1 at lower altitude followed by 70125 at higher altitude. The lichen biomass ranged between 5375 g ha-1 yr-1 to 7862.5 g ha-1 yr-1 in all the studied sites. Across the study sites seasonal highest biomass (11687 g ha-1) of fallen lichens was estimated in summer followed by 3198 in winter and 2950 during rainy season. Minimum biomass was recorded in spring season of about 2262 g ha-1. Similarly, annual highest biomass of fallen lichens was recorded 7862.5 g ha-1 at lower altitude. Quercus leucotrichophora, Pinus roxburghii and Rhododendron. arboreum trees were observed as luxuriant lichens particularly in lower altitude. Parmotrema praesorediosum contributes a maximum 85.37% biomass of all species at lower altitude. At higher altitude R. conduplicans contributes maximum 31.13% followed by P. tinctorum (27.70%) and E. cirrhatum (19.31%) of the total fallen lichen biomass.